Fetomaternal outcome and raised bilirubin level in pregnancy - Joshi, Ruchi; Dalal, Nilesh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Jaundice in pregnancy has potentially serious consequences for maternal and fetal health. The cardinal features of hepatobiliary disease may include jaundice, pruritus, abdominal pain; nausea, vomiting, and a variety of liver biochemical test abnormalitiesChallenges involve making the diagnosis and the methods of treatment and their safety for both the mother and the baby. Methods: Based on inclusion criteria, 120 pregnant women were selected from Department of Obstetrics & Gynecology, MGMMC and MYH Indore from 1Aug 2014 to 1st August 2015.Patients were categorized according to serum bilirubin level. Basic investigations done and associated complications studied and correlated according to the severity and degree of jaundice. Results: 60% of the patients were aged between 20 and 30 years. 54% were primigravida. 83.3% lived in rural areas while 74.27% came in emergency. Maternal mortality was found highest in the third trimester and when the serum bilirubin crossed 5mg/dl. 43.34% patients with jaundice developed acute kidney injury with serum creatinine level above the cut-off. INR was deranged in 47.5% of the patients. The most common complication seen in our study group was that of HELLP closely followed by multi organ dysfunction and encephalopathy. 67% of the patients delivered vaginally, while 20% went under LSCS. Maternal mortality was 32.5% and perinatal outcome was poor with 50% mortality and 25% nursery admission. 62% of the patients who died were referred from a peripheral health centre. Conclusions: Liver disease can cause significant morbidity and mortality in both pregnant women and their infants. Better identification and treatment of mothers and fetuses at risk may have far-reaching implications for maternal and child health. Monitored intensive care gives a long term pay off in the maternal and fetal outcome.